Analysis Quality for Kernel Production with Seven Tools Method - Nensi, Sri Wahyu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2025)
In today’s era of rapid industrial advancement, the palm oil industry in Indonesia has experienced significant growth, intensified competition and prompting companies to enhance production quality to remain competitive. Predominantly acting as raw material suppliers, many palm oil companies, including those in Southeast Sulawesi, are required to meet stringent quality standards set by their domestic and international partners. One such company processes oil palm into crude palm oil (CPO), palm kernel, fibre, and kernel shell, with CPO and kernel being distributed to partner companies under strict quality agreements. A breach of these agreements, particularly in kernel quality, has led to penalties and potential termination of partnerships. Palm kernel oil (PKO), a high-value derivative, must meet quality criteria such as free fatty acid content, moisture, dirt content, and kernel integrity. Observations revealed recurring deviations from these standards, notably in excessive dirt content. This study aims to identify root causes of quality issues using the Seven Quality Control Tools method, supported by primary data including production outputs and interviews with workers. The analysis identified key contributing factors: inadequate adherence to machine efficiency guidelines by operators, sorting errors in raw materials, and mismatched or poorly maintained machinery. Corrective actions were proposed using 5W+1H analysis, emphasizing the need for operator compliance with efficiency protocols, improved raw material handling, and appropriate machine usage and maintenance to ensure consistent kernel quality aligned with agreed standards.